A study of knee anterior cruciate ligament biomechanics with respect to energy and relaxation. (December 2020) - Cui, Ze; Chen, Zenghao; Qian, Donghai; Yang, Hongxin; Huang, Saishuai; Zhu, Danjie; Zhang, Hongbo
Abstract: Background: This research aimed to study the biomechanical properties of sheep tendon under torsion and the tendon energy absorption performance with an externally imposed initial force. Methods: Tendons of nine healthy knees of sheep were investigated. In both tests, we investigated energy and relaxation at rotations of 0°, 90°, 180°, and 360°. For both tensile force and tensile displacement at a sampling period of 100 milliseconds, the maximum value of 89 N was selected as the maximum tension state for 600 s of relaxation duration for testing relaxation, and analysed of the average force of the last 30 s. Findings: The difference of energy levels of the tendons are significant between twisted groups (180° and 360°) and untwisted group (0°) ( P < 0.05); The relaxation force decreases significantly with twisted groups (90°, 180°, and 360°) and untwists group (0°) ( P < 0.05). The nine-group tendons show no significant difference at torsion 90° and 180° ( P = 0.466). Peak force test shows significant differences between the twisted groups (90°, 180°, and 360°) and untwisted group (0°) ( P < 0.05). Interpretation: The torsion tendon has lower energy absorption and relaxation than the untwisted counterparts; thus, it may be more prone to damage. These results are useful for providing guidance on anterior cruciate ligament reconstruction. Highlights: The viscoelasticity behaviour an energy and relaxation model initial prosthesis use. Torsion of the graft resulted in a decrease in viscoelasticity. Torsion increased risk of anterior cruciate ligament injury.